Performance Analysis and Reduction of Torque Ripple of Axial Flux Permanent Magnet Synchronous Motor Manufactured for Electric Vehicles - Polat, Mehmet; Yildiz, Ahmet; Akinci, Ruya (Ieee-Inst Electrical Electronics Engineers Inc, 2021)
Axial flux permanent magnet synchronous motors (AFPMSMs) have advantages over other motor types in terms of efficiency, vibration, and noise. However, torque ripple is an important problem for axial flux permanent magnet (AFPM) motors. One of the methods recommended as a solution to this problem is the skew operation. The skew can be applied to the magnets or the stator. However, for these motors, this process is mostly applied to magnets because the skew applied to the stator makes it difficult to manufacture. In this article, a solution to the torque ripple of an in-wheel AFPMSM for the electric vehicle is sought. For this purpose, designs, optimization, and 3-D analyzes have been carried out. This solution has been applied to magnets designed by skewing for ease of production. 3-D analyses have been carried out by applying skew of up to 40 degrees with an angle of 5 degrees to the magnets in the rotor. In light of the analysis, the most appropriate skew angle that does not affect motor performance has been determined. As a result of the analysis of the motor model obtained with the determined skew angle, it is observed that the torque ripple decreased by 86.71%. Finally, production has been carried out according to the analysis results obtained.
Keywords: Axial flux permanent magnet (AFPM) synchronous; electrical vehicle; finite element method (FEM); skew; torque ripple